Detection of recurrent cutaneous angiosarcoma of lower extremity with 18 F-fluorodeoxyglucose positron emission tomography-computed tomography: Report of three cases - Punit Sharma; Harmandeep Singh; Abhinav Singhal; Chandrasekhar Bal; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2013)
Cutaneous angiosarcomas (CAS) are uncommon, aggressive tumours. Very rarely, they arise from the lower extremity. Such tumours are usually associated with chronic lymphedema, a phenomenon known as Stewart-Treves Syndrome. Treatment is usually radical surgery with adjuvant therapy (radiotherapy/chemotherapy). Recurrence rate after primary treatment is high. Because of post therapy changes, conventional imaging has limited specificity for diagnosing recurrence. 18 F-Fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET-CT) might be useful in such patients. It can demonstrate local recurrence along with distant metastasis, if any and can have significant impact on patient management. We here present three cases of recurrent CAS of lower extremity diagnosed with 18 F-FDG PET-CT.